Docência no ensino superior: conhecimentos profissionais e processos de desenvolvimento profissional - Mussi, Amali de Angelis (2007)
This study it establishes as main focus of inquiry the professional knowledge that establish the pedagogical practice of teachers who works teaching in superior education. Consequently, the studies developed around the type and of the nature of the knowledge that are in the base of performance of the professor acquire basic importance for the development of this inquiry, in special the works of Shulman (1986, 1987, 1996) and of its collaborators, regarding the types of professional knowledge and forms of pedagogical reasoning; of Placco (2006) and Tardif, Lessard and Lahaye (1991) in relation to knowing them of tecahing; beyond Tardif (2002), on the sources of acquisition of knowing professors to them, relating them with its ways of integration in the teaching work. With different theoretical-methodology perspectives, these inquiries detach the character of continuity of the teaching professional development; they face the professor as professional capable to recognize and to decide questions of its practical professional, constructing, reconstructing, organizing and using specific knowledge of teathing. When searching in pertinent literature the instrument that could be used in the inquiry of the professional knowledge of university professors, we find the studies developed for Nineth (2001, 2005), Mizukami (2000, 2002), Merseth (1996), Shulman, L. (1986, 1987), amongst others, concerning the nature of the teaching knowledge. Such studies focus education cases as basic instruments for the inquiry of the processes of teaching professional development, amongst other possibilities of use. In this inquiry we look for to apprehend which the professional knowledge that base practical the pedagogical professor can if evidenced for professors of superior education, by means of education cases. For its accomplishment, in period 2005/2006, four university professors had analyzed education cases that contemplated pertaining to school situations faced by different professors of superior education and had elaborated a case of education from the experiences lived in superior education. In general way, the strategies of analysis and elaboration of education cases had allowed to apprehend to know of the teaching and its sources to them, as well as different types of knowledge that are in the base of its professional performance and its processes of pedagogical reasoning. They had evidenced doubts, reasons, conflicts that guide and characterize its practical professionals. They showed involved processes of reflection in the education of the professors and had ahead stimulated its reflexive position of the pertaining to school situations. They had shown the complexity that characterizes the teaching in superior education, and they had evidenced that the use of education cases if constituted in important strategy of inquiry to promote processes of professional development